Obesity Promotes Extracellular Matrix and Metabolic Proteins Network in Aortic Stenosis. (9th April 2021) - Bouchareb, Rihab; Guaque-Orlate, Sandra; Snider, Justin; Zaminski, Devyn; Anyanwu, Anelechi; Stelzer, Paul; Lebeche, Djamel
Abstract : Objective : Obesity is one the main risk factors promoting the progression of aortic stenosis. Today, there is a critical need to identify new therapeutic targets to reverse or stop the progression of aortic stenosis. This study aimed to evaluate the modulation of extracellular matrix proteins (ECM) and its impact on metabolic enzymes during aortic valve mineralization. Methods : We analyzed ECM markers expression by mass spectrometry and RNA sequencing on explanted human aortic valves and isolated human valve cells, in 2 independent human cohorts (n= 15 vs n=17). Results : We identified a complex linkage between calcified and fibrotic phases, with an elaborate interaction between ECM, metabolic, complement and lipid transporter proteins. Aldehyde Dehydrogenase 1 Family Member A1 (ALDH1), a major enzyme in alcohol metabolism, was down regulated in both fibrotic and calcified stages. We identified Fibronectin Type III Domain Containing 1 (FNDC1) and Matrix-remodeling Associated 5 (MXRA5) as the common modulated ECM protein in calcified valve tissue in both proteomic and RNAseq data sets. Conclusion : This work highlights the interactome between metabolic and ECM markers, and identified FNDC1 and MXRA5 as novel ECM markers in calcified valves, electing them as potential targets in the development and the progression of AS.